KARAKTERISTIK BRIKET TONGKOL JAGUNG DAN SERBUK GERGAJI KAYU DENGAN PEREKAT TAPIOKA - Saputra, Niko; Hamzah, Farida Hanum; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study was to determine the characteristics of charcoal briquette from a mixture of corncob and sawdust seed quality according to SNI 01-6235-2000. Research using completely randomized design (CRD) with charcoal treatment comparison corncob and sawdust (P1= 100:0%); (P2= 75:25%); (P3= 5%:50%); (P4= 25:75%); (P5= 0:100%). The result showed that variations in mix charcoal corncob and sawdust significantly affect the moisture content, ash content, calorific value, volatile matter, and fixed carbon content briquettes. The result showed that the best treatment in treatment P4 namely charcoal briquettes are made with 25% charcoal corncob and 75% charcoal sawdust with levels of moisture content 6.238%, ash content 6.889%, calorific value 5714 cal. g-1, volatile matter 11.277%, and fixed carbon content 78.89%. Keywords: Charcoal briquettes, corncob, sawdust